Penerapan Model Pembelajaran Make a Match Berbantuan Media Wordwall Untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa Kelas 2 SDN 44 Mataram - Ayisah, Miftahul Ayisah; Sukarso, A.A; Wirawan, Mohamad Junaidin (Mataram University, 2025)
This study aims to analyze the effectiveness of the Make a Match learning model assisted by Wordwall media in improving the activeness and learning outcomes of second-grade students at SDN 44 Mataram. The research employed a quantitative approach using a classroom action research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles. The subjects consisted of 17 students. Data collection techniques included observation to measure student activeness, learning achievement tests to assess improvement in understanding, and documentation as supporting data. The results showed that the implementation of the Make a Match model assisted by Wordwall significantly increased students’ learning activeness. In the first cycle, student participation was categorized as moderate, but after improvements in the second cycle, participation increased notably. This enhancement also had a positive impact on learning outcomes, as the students’ average scores rose from 65 in the first cycle to 85 in the second cycle. Therefore, the Make a Match model assisted by Wordwall proved effective in creating an interactive and enjoyable learning atmosphere, while improving both student activeness and learning outcomes.